Analisis Atraksi Amenitas dan Aksesibilitas dalam Meningkatkan Kepuasan Wisatawan (Studi Kasus Pantai Biru Kersik Marangkayu Kabupaten Kutai Kartanegara) - Opilia Arpiani Putri; Ana Noor Andriana (Jurnal Kajian dan Terapan Pariwisata, 2021)
Attractions, amenities and accessibility are factors that determine success in the development of tourist destinations. The development of tourism product components such as attractions, amenities and accessibility allow managers to increase the number of visits and tourist satisfaction. Kersik Village has a strategic marine tourism potential, namely Blue Kersik Beach. Blue Kersik Beach is a natural tourist destination in Kersik Village, Marangkayu District, Kutai Kartanegara Regency. Cooperation between the government and tourism awareness groups in increasing tourist satisfaction is through attractions, amenities and accessibility. Based on the data obtained by the researchers, it is known that the phenomenon that occurs at Biru Kersik Beach is the lack of maintenance of amenities that affect the satisfaction of visiting tourists. This study aims to identify and analyze attractions, amenities and accessibility as well as supporting factors and inhibiting factors for increasing tourist satisfaction. This research uses qualitative research with a case study approach. This study found that (1) tourist attractions were adequate, but some tourists mentioned the need for additional tourist activities so that the purpose of visiting Biru Kersik Beach was not only to enjoy the beach panorama; (2) amenities in the form of public facilities and supporting facilities; (3) accessibility has been fulfilled which makes it easier for tourists to get to Biru Kersik Beach; (4) inhibiting factors of the tourist attraction of Blue Kersik Beach; and (5) inhibiting factors for the lack of skilled human resources in the field of tourism, promotion on social media, and limited funds.